Mechanobiological Bone Reaction Quantified by Positron Emission Tomography. (May 2015) - Suenaga, H.; Chen, J.; Yamaguchi, K.; Li, W.; Sasaki, K.; Swain, M.; Li, Q.
While nuclear medicine has been proven clinically effective for examination of the change in bone turnover as a result of stress injury, quantitative correlation between tracer uptake and mechanical stimulation in the human jawbone remains unclear. This study aimed to investigate the relationship between bone metabolism observed by 18F-fluoride positron emission tomography (PET) images and mechanical stimuli obtained by finite element analysis (FEA) in the residual ridge induced by the insertion of a removable partial denture (RPD). An 18F-fluoride PET/CT (computerized tomography) scan was performed to assess the change of bone metabolism in the residual ridge under the denture before and after RPD treatment. Corresponding patient-specific 3D finite element (FE) models were created from CT images. Boundary conditions were prescribed by the modeling of condylar contacts, and muscular forces were derived from the occlusal forces measured in vivo to generate mechanobiological reactions. Different mechanobiological stimuli, e.g., equivalent von Mises stress (VMS), equivalent strain (EQV), and strain energy density (SED), determined from nonlinear FEA, were quantified and compared with the standardized uptake values (SUVs) of PET. Application of increased occlusal force after RPD insertion induced higher mechanical stimuli in the residual bone. Accordingly, SUV increased in the region of residual ridge with higher mechanical stimuli. Thus, with SUV, a clear correlation was observed with VMS and SED in the cancellous bone, especially after RPD insertion (R 2 > 0.8, P < 0.001). This study revealed a good correlation between bone metabolism and mechanical stimuli induced by RPD insertion. From this patient-specific study, it was shown that metabolic change detected by PET in the loaded bone, in a much shorter duration than conventional x-ray assessment, is associated with mechanical stimuli. The nondestructive nature of PET/CT scans and FEA could potentially provide a new method for clinical examination and monitoring of prosthetically driven bone remodeling.